2014
DOI: 10.1136/bmjresp-2014-000057
|View full text |Cite
|
Sign up to set email alerts
|

Sequencing of idiopathic pulmonary fibrosis-related genes reveals independent single gene associations

Abstract: BackgroundPrevious studies investigating a genetic basis for idiopathic pulmonary fibrosis (IPF) have focused on resequencing single genes in IPF kindreds or cohorts to determine the genetic contributions to IPF. None has investigated interactions among the candidate genes.ObjectiveTo compare the frequencies and interactions of mutations in six IPF-associated genes in a cohort of 132 individuals with IPF with those of a disease-control cohort of 192 individuals with chronic obstructive pulmonary disease (COPD)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
51
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(59 citation statements)
references
References 38 publications
3
51
1
Order By: Relevance
“…Transmission is autosomal dominant [90,91]. In selected cases of familial ILD, study of SFTPA2, SFTPC and ABCA3 allowed a genetic cause to be identified in 6.5% of families [92].…”
Section: Surfactant Protein Mutationsmentioning
confidence: 99%
“…Transmission is autosomal dominant [90,91]. In selected cases of familial ILD, study of SFTPA2, SFTPC and ABCA3 allowed a genetic cause to be identified in 6.5% of families [92].…”
Section: Surfactant Protein Mutationsmentioning
confidence: 99%
“…Premature infants with underdeveloped lungs often become hypoxic and die due to a high surface tension at the epithelial layer due to the under-expression of surfactant lipids [69,70]. In IPF, mutations occur in the surfactant genes SFTPC [71][72][73][74], SFTPA2 [75], and ABCA3 [76]. The IPF variants in these genes lead to misfolded and shortened proteins and aberrant expression [77].…”
Section: Surfactantmentioning
confidence: 99%
“…The disease is characterised by progressive worsening of dyspnoea and lung function and is generally associated with a poor prognosis (1). Although the aetiology of IPF is unknown, the pathogenesis is believed to involve both genetic predisposition and environmental risk factors, including smoking, exposure to metal and wood dust, gastro-oesophageal reflux disease (GORD) and even some viral infections (2).…”
Section: Introductionmentioning
confidence: 99%